Middleware implementation for RYU SDN Controller to manage switches in a C-RAN scenario - Nóvoa, Lucas; Tavares, Virgínia; Nahum, Cleverson; Lins, Silvia; Klautau, Aldebaro (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2021: Anais do XLVIII Seminário Integrado de Software e HardwareDO - 10.5753/semish.2021.15803, 2021)
With the advent of 5G, more stringent application requirements were imposed to the cellular networks. The adoption of Software Defined Network (SDN) technology in the transport network enables more dynamic network control, suitable for several real-time operations and use cases present in 5G deployments. Implementing testbed for various transport network scenarios is not trivial due to the high costs involved, especially with respect to hardware in more complex network topologies. This work provides a low-cost alternative that facilitates complex transport network topologies implementation in real testbeds. It adopts Mininet software for transport network emulation and implements a middleware that facilitates the control of flows and routes as well as the automatic recognition of any topology. In networking research domain, the implemented middleware contributes to the simplification of switches management in software defined networks scenarios.